Die Verbreitung der Holzarten im Oberengadin unter dem Einfluss des Menschen und des Lokalklimas - Holtmeier, Friedrich-Karl (ERDKUNDE, 1967)
Larch-cembra-pine forests are typical of the inner alpine regions with their continental climate. A certain differentiation between stands of larch and cembra-pine is to be observed. Cembra-pine is mainly spread on steep and inaccessible slopes and north exposures, whereas larch dominates on easily accessible locations exposed to the South. This situation is typical for the Oberengadin too. The distribution of larch and cembra-pine is conditioned to a great extent by human influences especially alpine farming. Since cembra-pine prevents the growth of grass and herbs, which larch does not, it was cleared on sunny and accessible slopes and restricted to the a. m. stands. In our days, after the ceasing of intensive alpine farming, cembra-pine can resettle these abandoned localities and the natural succession from larch to larch-cembra-pine forest, which had been interupted and delayed for some hundred years goes on again. An effect of a special local-climatic situation is the distribution of spruce. Spruce is frequent only on the right side (NW-exposure) of the main valley between the village Sils and the small Lake of Staz within the normal larch-cembra pine forest. That is exactly the area where a cloud belt, the so-called Malojaschlange (Holtmeier, 1966 a), which appears when the Oberengadin is influenced by barometric depressions in the Mediterranean region, lasts an extremely long time. The Krummholz of Pinus montana and Alnus viridis is typical for slopes endangered by snow-avalanches, rock falls, and torrential washes. By their elasticity which enables them to resist injury from these factors they are adapted to these stands. A quite strong differentiation by southerly and northerly aspect can be observed in the distribution of Pinus montana and Alnus viridis. Pinus montana is spread on slopes dry and exposed to the South whereas Alnus viridis dominates on north exposures. The reason for this distribution can be explained by the different rate of humidity.